The Role of Technology in the Development of Arabic Language Education in Indonesia - Ahmad Zaky; Muhammad Sapii Harahap; Ade Muhammad Ritonga (Edumaspul: Jurnal Pendidikan, 2023)
In this global era, like it or not, we have to deal with technology, especially information technology. This is because the technology has affected our daily lives. Therefore, we should not 'stutter' technology. Many research results show that those who are late in mastering information, then it is too late to get opportunities to advance. This is as stated by Alfin Toffler that those who do not master science and technology, then their position will be marginalized and they will be blown away by the wave of globalization which is full of competition. In this modern era, information and communication technology has developed so rapidly. Information and communication technology has penetrated and penetrated so deeply into various aspects of human life. The application of information technology in education is a real and factual challenge. It is undeniable that advances in information technology have had a positive impact on the advancement of education today. Especially computer and internet technology, both in terms of hardware and software, provide many offers and choices for the world of education to support the learning process. The advantage offered lies not only in the speed factor for obtaining information but also in multimedia facilities that can make learning more interesting, audiovisual and interactive. In line with the development of internet technology, many learning activities can be carried out by utilizing this technology.